2008
DOI: 10.1124/dmd.108.020404
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of Lasofoxifene, a Next-Generation Selective Estrogen Receptor Modulator, in Healthy Male Subjects

Abstract: Postmenopausal women have an increased risk of developing osteoporosis as their levels of endogenous estrogen decrease (Luisetto et al

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
2
15
1
Order By: Relevance
“…Prakash, et al reported previously that neither catechol nor glutathione conjugates of LAS were detected in humans or preclinical species, and concluded that this was likely due to rapid conjugative metabolism (O-methylation, glucuronidation, or sulfation) followed by urinary excretion. 31 However, results of the present study suggest that LAS- o -quinone formation and subsequent thiol conjugation could represent a possible competing pathway, as GSH conjugates were observed alongside glucuronidated or O-methylated metabolites in incubations containing GSH in the presence of glucuronidating or methylating systems (Figure 4). Although LAS GSH conjugates have not been previously detected in vivo , our data clearly demonstrate that LAS catechols may further oxidize to thiophilic o -quinones.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Prakash, et al reported previously that neither catechol nor glutathione conjugates of LAS were detected in humans or preclinical species, and concluded that this was likely due to rapid conjugative metabolism (O-methylation, glucuronidation, or sulfation) followed by urinary excretion. 31 However, results of the present study suggest that LAS- o -quinone formation and subsequent thiol conjugation could represent a possible competing pathway, as GSH conjugates were observed alongside glucuronidated or O-methylated metabolites in incubations containing GSH in the presence of glucuronidating or methylating systems (Figure 4). Although LAS GSH conjugates have not been previously detected in vivo , our data clearly demonstrate that LAS catechols may further oxidize to thiophilic o -quinones.…”
Section: Discussionmentioning
confidence: 59%
“…30 The structural resemblance to E 2 led us to hypothesize that LAS would form similar quinoid metabolites (Scheme 1). It has been previously reported that 5-hydroxylasofoxifene (5-OHLAS) and 7-hydroxylasofoxifene (75OHLAS) catechols are formed as primary oxidative metabolites of LAS; 31 however, the potential for further oxidation of these catechols to electrophilic quinoids has not been investigated. In the current study, we have found that LAS can be oxidized both chemically and enzymatically to o -quinones which form conjugates with GSH.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the structures of the metabolites, six metabolic pathways of LAS were identified: hydroxylation at the tetraline ring, hydroxylation at the phenyl rings attached to tetraline, methylation of the catechol intermediates by catechol-O-methyl transferase, conjugation with glucuronic acid and sulfuric acid, and oxidation at the pyrrolidine ring. All the human metabolites were observed in at least one of the species (Prakash et al, 2008). In addition, the exposure of major circulating metabolites in these test species was higher relative to humans at proposed therapeutic doses, suggesting that the preclinical test species were suitable models for assessing safety (http:// www.fda.gov/cder/guidance/index.htm).…”
Section: Discussionmentioning
confidence: 99%
“…Based on its clearance values, it is likely that first pass hepatic metabolism is largely responsible to the attenuation of moderate bioavailability in rats (25%) and monkeys (55%). In humans, LAS is eliminated by both phase I oxidative metabolism mediated primarily by CYP3A4 and CYP2D6 isozymes and by phase II conjugation (Prakash et al, 2008). Metabolic pathways of drug candidates in animals, used for safety evaluation studies, are required to ensure that the selected animal species are exposed to all major metabolites (Ͼ10% parent AUC) formed in humans (Baillie et al, 2002; http:// www.fda.gov/cder/guidance/index.htm).…”
mentioning
confidence: 99%
“…Oxidation of lasofoxifene is primarily catalyzed by CYP3A4/3A5 and CYP2D6 and leads to the formation of isomeric phenols followed by conjugation ( Figure A.10 ) (Prakash et al, 2008 ).…”
Section: A62 Polymorphism Of Dme Smentioning
confidence: 99%